Impact of Standard Setting Methodologies overPassing Scores - Sevda ÇETİN; Selahattin GELBAL (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
In this study impact of standard setting methodologies over passing scores is studied and the changes on students’ pass/fail scores using different setting methodologies are researched. The data of the research in the first phase is collected from test results which are developed by researcher using 25 items per Turkish Language and Mathematics exams and applied to 129, 7th grade, Elementary School students. The data for second phase are collected by calculating cut points standing on different expert judgments per different methodology. It is seen by this study that the decision on standard setting methodologies for the students are related to students group, the structure of test methods and instructors